Status Gizi Remaja Putri Di Puskesmas Klaten Selatan - Prihati, Dwi Retna; Nurrasyidah, Rahmi; Kuswati, Kuswati (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Background: Malnutrition in adolescents can cause effects on stunted physical growth and psychological development. The method used to measure is anthropometric assessment by measuring body mass index (BMI) and upper arm circumference. Objective: To describe the nutritional status of adolescent girls in the South Klaten Health Center. Methods: Research quantitative description with observational method using cross sectional design. The number of samples that became respondents was 119 taken with the technique of concecutive random sampling. Research location in South Klaten Health Center. Results: Respondents BMI was normal nutritional status 73 people (61%), thin 19 people (16%), very thin 15 people (13%), fat 8 people (7%) and obese 4 people (3%). Upper arm circumference Respondents were (Normal 23.5 – 28.5 cm) 72 people (61%), (less< 23.5) 42 people (35%) and (more> 28.5 cm) 5 people (4 %). Conclusion: The majority of adolescent girls have normal nutritional status. Suggestion: Malnourished respondents must consume food as needed.